2020
DOI: 10.1101/2020.08.25.20181487
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 hospitalisation rates rise exponentially with age, inversely proportional to thymic T-cell production

Abstract: Here we report that COVID-19 hospitalisation rates follow an exponential relationship with age, increasing by 4.5% per year of life (95% CI: 4.2-5.2%). This mirrors the exponential decline of thymus volume and T-cell production (decreasing by 4.5% per year). COVID-19 can therefore be added to the list of other diseases with this property, including those caused by MRSA, West Nile virus, Streptococcus Pneumonia and certain cancers, such as chronic myeloid leukemia and brain cancers. In addition, incidence of se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Both disease risk and thymic output are described by exponential functions that double and halve every 16 years, respectively 18 . Interestingly, this correlation also holds true for COVID-19 susceptibility 19 .…”
Section: Thymic Function At the Extreme Ends Of Lifementioning
confidence: 56%
“…Both disease risk and thymic output are described by exponential functions that double and halve every 16 years, respectively 18 . Interestingly, this correlation also holds true for COVID-19 susceptibility 19 .…”
Section: Thymic Function At the Extreme Ends Of Lifementioning
confidence: 56%
“…115,123 There are plenty of studies which revealed that in certain cases, various prophylactic measures used to prevent the spread of SARS-CoV-2 and other viruses and bacteria, could have negative effects on the human body, have low efficacy or may even be useless in terms of prevention of diseases. Since the main target for SARS-CoV-2 are people with the weak immunity, 13,[40][41][42] and prolonged mental stress affects both the entire body, [124][125][126]236 and the immune system in particular, [237][238][239][240][241] a new study is needed to answer the question, if medical and non-medical measures used to prevent the spread of SARS-CoV-2 could affect natural immunity. This question is especially relevant for countries which had a dramatic increase in cases and deaths during the third phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…115,123 There are plenty of studies which revealed that in certain cases, various prophylactic measures used to prevent the spread of SARS-CoV-2 and other viruses and bacteria, could have negative effects on the human body, have low efficacy or may even be useless in terms of prevention of diseases. Since the main target for SARS-CoV-2 are people with weak immunity, 13,[40][41][42] and prolonged mental stress affects both the entire body, 124-126,254 and the immune system in particular, [255][256][257][258][259] a new study is needed to answer the question, if medical and non-medical measures used to prevent the spread of SARS-CoV-2 could affect natural immunity. This question is especially relevant for countries which had a dramatic increase in cases and deaths during the third phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…40,96 The risk of COVID-19 hospitalization rises exponentially with age, inversely proportional to T-cell production. 41 In COVID patients, thymus enlargement was frequent and associated with increased T-lymphocytes production that appears to be a beneficial adaptation to virus-induced lymphopenia. The loss of thymic reactivation might contribute to a worse prognosis.…”
Section: Paradoxes Of Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation